Multiple Gibberellin Receptors Contribute to Phenotypic Stability under Changing Environments - Illouz-Eliaz, Natanella (Plant Cell, 2019)
The pleiotropic and complex gibberellin (GA) response relies on targeted proteolysis of DELLA proteins mediated by a GA-activated GIBBERELLIN-INSENSITIVE DWARF1 (GID1) receptor. The tomato (Solanum lycopersicum) genome encodes for a single DELLA protein, PROCERA (PRO), and three receptors, SlGID1a (GID1a), GID1b1, and GID1b2, that may guide specific GA responses. In this work, clustered regularly interspaced short palindromic repeats (CRISPR) /CRISPR associated protein 9–derived gid1 mutants were generated and their effect on GA responses was studied. The gid1 triple mutant was extremely dwarf and fully insensitive to GA. Under optimal growth conditions, the three receptors function redundantly and the single gid1 mutants exhibited very mild phenotypic changes. Among the three receptors, GID1a had the strongest effects on germination and growth. Yeast two-hybrid assays suggested that GID1a has the highest affinity to PRO. Analysis of lines with a single active receptor demonstrated a unique role for GID1a in protracted response to GA that was saturated only at high doses. When the gid1 mutants were grown in the field under ambient changing environments, they showed phenotypic instability, the high redundancy was lost, and gid1a exhibited dwarfism that was strongly exacerbated by the loss of another GID1b receptor gene. These results suggest that multiple GA receptors contribute to phenotypic stability under environmental extremes.